Morphometric Identification of Starch Granules From Archaeological Contexts: Diagnostic Characteristics of Seven Major North American Plant Families - Louderback, Lisbeth A.; Wilks, Stefania; Herzog, Nicole M.; Brown, Gloria Howat; Joyce, Kaley; Pavlik, Bruce M. (Frontiers in Earth Science, 2022)
Starch-rich plants have played an important role in human evolution and societal development. Collected, grown, and consumed to support ever-increasing populations, such plants are integral to understanding past human diets. With the advent of starch granule analysis, plant resources that were invisible in the archaeological record can now be revealed in the cracks and crevices of artifacts. Widespread application of this technique, however, has stalled due to a lack of rigorous and standardized protocols. For example, taxonomic identification of starch granules using consistent diagnostic characteristics is still a challenge as there are no comprehensive surveys across important (i.e. dietary) plant taxa, especially at the levels of families, genera, and species. This study provides characteristics for identifying starch granules of seven major North American plant families (Amaranthaceae, Apiaceae, Fagaceae, Liliaceae, Pinaceae, Poaceae, and Solanaceae) based on systematic, morphometric studies of modern reference materials. A dichotomous key to starch granules of the seven families was also generated to aid in identification of those from archaeological contexts. Although we have focused on plants from western North America, these families occur across the globe and have had dietary significance throughout prehistory.